The Influence of Physical Work Environment and Social Work Environment on Individual Performance in Sinar Mas Land - mario julian prakoso; ra afera ratna wijayanti; muhammad affandi (IULI Publisher, 2023)
Human resource is the key driver in any organization and will determine the success of the organization. Individual performance is one of the indicators to how welldoes an employee performance is towards the company. How well does an employee performs can be determined by their individual performance. The individual performance does have factors which are the Physical Work Environment, and Social Work Environment. The physical work environment and social work environment are the x variables to find which of them the main influence that affects the individual performance is. The purpose of this research is to determine how influential are physicalwork environment and social work environment towards the individual performance ofthe corporate communications division in Sinar Mas Land. This research thesis uses the quantitative research method. The data is collectedusing primary data and secondary data. The primary data is gathered usingquestionnaires through Google forms, and the secondary data is using journal articles, and websites. The questionnaire is distributed to 115 respondents of Sinar Mas Land, and to process the data, this thesis use IBM SPSS Statistics 23 and AMOS 25 Graphics toconduct analysis and to test the hypothesis. Keywords: Human Resource, Physical Work Environment, Social Work Environment, Individual Performance